Phenolic Fractions from Vaccinium vitis-idaea L. and Their Antioxidant and Anticancer Activities Assessment - Vilkickyte, Gabriele (Antioxidants (Basel), 2020)
Lingonberry leaves and fruits are associated with a range of potential bioactivities related to their phenolic content and composition, but the identification of major biological activity markers remains limited. The present study aimed at the isolation of lingonberry phenolic fractions and biological activity evaluation of them. Crude dry extracts of lingonberry leaves and fruits were fractionated by chromatography using Sephadex LH-20 and analyzed by validated HPLC-PDA method. For each fraction, the anticancer activity against human clear cell renal cell carcinoma (CaKi-1), human colon adenocarcinoma (HT-29), and human malignant melanoma (IGR39) cell lines was determined using MTT assay, and the radical scavenging, reducing, and chelating activities were investigated using ABTS, FRAP, and FIC assays, respectively. Further, 28 phenolics were identified and quantified in the crude extract of lingonberry leaves and 37 in the extract of fruits. These compounds, during fractionation steps, were selectively eluted into active fractions, enriched with different groups of phenolics—monophenols, anthocyanins, phenolic acids, catechins, flavonols, or proanthocyanidins. Fractions of lingonberry leaves and fruits, obtained by the last fractionation step, proved to be the most active against tested cancer cell lines and possessed the greatest antioxidant activity. In this perspective, the predominant compounds of these fractions—polymeric and mainly A-type dimeric proanthocyanidins—also quercetin can be considered to be anticancer and antioxidant activity markers of lingonberries.